2011
DOI: 10.1063/1.3599697
|View full text |Cite
|
Sign up to set email alerts
|

Mach 5 bow shock control by a nanosecond pulse surface dielectric barrier discharge

Abstract: Bow shock perturbations in a Mach 5 air flow, produced by low-temperature, nanosecond pulse, and surface dielectric barrier discharge (DBD), are detected by phase-locked schlieren imaging. A diffuse nanosecond pulse discharge is generated in a DBD plasma actuator on a surface of a cylinder model placed in air flow in a small scale blow-down supersonic wind tunnel. Discharge energy coupled to the actuator is 7.3–7.8 mJ/pulse. Plasma temperature inferred from nitrogen emission spectra is a few tens of degrees hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(78 citation statements)
references
References 18 publications
2
73
0
3
Order By: Relevance
“…Also, compression waves generated in a NS-DBD actuator placed on the surface of a cylinder model in a Mach 5 flow were demonstrated to strongly perturb the bow shock in front of the model, which increased the shock stand-off distance, as shown in Fig. 3 [15].…”
Section: Introductionmentioning
confidence: 98%
“…Also, compression waves generated in a NS-DBD actuator placed on the surface of a cylinder model in a Mach 5 flow were demonstrated to strongly perturb the bow shock in front of the model, which increased the shock stand-off distance, as shown in Fig. 3 [15].…”
Section: Introductionmentioning
confidence: 98%
“…Another interesting future study is based on the position control of impinging oblique shock waves through pressure waves generated by ns-DBD's, based on a similar outcome shown by Nishihara et al 30 examining bow shocks. Of course, these are just two examples of possible areas of future research that can be conducted.…”
Section: Energy Deposition Methods For Sbli and Boundary Layer Smentioning
confidence: 99%
“…This has benefits in improving the drag characteristics and reducing heat transfer. Nishihara et al 30 demonstrated that this was possible by applying a surface ns-DBD plasma actuator to a cylinder in a Mach 5 flow (a schematic of the ns-DBD used for this experiment is shown in figure 10). They achieved an increased stand-off distance of the bow shock by up to 25%.…”
Section: Applications Of Ns-dbdmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of vibrationally and electronically excited species in a hypersonic flow may strongly affect the emission signature from the shock layer. Finally, short-pulse electric discharges efficiently loading electronic energy levels of nitrogen and oxygen in air are currently being explored as means of hypersonic flow control by producing repetitive localized pressure perturbations in the flow [3].…”
Section: Introductionmentioning
confidence: 99%